Iron Superoxide Dismutase Protects against Chilling Damage in the Cyanobacterium Synechococcus species PCC7942 - Thomas, David J. (American Society of Plant Physiologists, 1999)
A strain of Synechococcus sp. PCC7942 lacking functional Fe superoxide dismutase (SOD), designated sodB(−), was characterized by its growth rate, photosynthetic pigments, inhibition of photosynthetic electron transport activity, and total SOD activity at 0°C, 10°C, 17°C, and 27°C in moderate light. At 27°C, the sodB(−) and wild-type strains had similar growth rates, chlorophyll and carotenoid contents, and cyclic photosynthetic electron transport activity. The sodB(−) strain was more sensitive to chilling stress at 17°C than the wild type, indicating a role for FeSOD in protection against photooxidative damage during moderate chilling in light. However, both the wild-type and sodB(−) strains exhibited similar chilling damage at 0°C and 10°C, indicating that the FeSOD does not provide protection against severe chilling stress in light. Total SOD activity was lower in the sodB(−) strain than in the wild type at 17°C and 27°C. Total SOD activity decreased with decreasing temperature in both strains but more so in the wild type. Total SOD activity was equal in the two strains when assayed at 0°C.